Comparación de las propiedades físicas, químicas, mecánicas y energéticas del biocombustible sólido obtenido a partir de la cáscara de Theobroma Bicolor, Theobroma Cacao L., Theobroma Grandiflorum , Iquitos-2024 - Santana Ahuanari, Mili Teresa Ayde (2025)
The general objective of the research was to establish the differences that exist between the physical, chemical, mechanical and energetic properties of solid biofuels obtained from the shell of Theobroma bicolor, Theobroma cacao L., Theobroma grandiflorum. The study population was made up of all the shells of the three species of the Theobroma family that are sold in the markets of Belén and Modelo in the province of Maynas. The sampling was non-random at the discretion of the authors of the research, the sample size was 3000 g. of shells for each species. The average values obtained with respect to the carbonization temperature of the shells were: carbonization temperature and time 280|C for 15 min, for the three varieties of shells. The results of the physical properties of the solid biofuel obtained were for Theobroma bicolor: density (0.43 g/cm3), humidity (34.25%); for Theobroma cacao L.: density (0.57 g/cm3 ), humidity (35.94%); for Theobroma grandiflorum. : density (0.53 g/cm3 ), humidity (37.01%). The energetic properties were for Theobroma bicolor.: Calorific value (8128.59 Cal/g.), flammability time (25 min); for Theobroma cacao L.: Calorific value (7490.49 cal/g.), flammability time (26 min); for Theobroma grandiflorum. : Calorific value (8216.26 cal/g.), flammability time (24 min). The mechanical properties with respect to the maximum compression load were for Theobroma bicolor. : (89.0 Kgf ); for Theobroma cacao L. (10.50 Kgf); for Theobroma grandiflorum. (84.50 Kgf). When comparing the values obtained regarding the physical properties of the solid biofuels obtained; the highest density corresponds to the solid biofuel obtained from the shell of Theobroma cacao L., the highest humidity corresponds to that of Theobroma grandiflorum.; Regarding the energetic properties it is established that the highest calorific value corresponds to the solid biofuel obtained from the shell of Theobroma grandiflorum. , the longest flammability time corresponds to that of Theobroma cacao L. and regarding the mechanical properties the maximum compression load corresponds to that of Theobroma bicolor